OPTIMIZING THE PREVENTION AND CONTROL OF STUNTING WITH FLIP SHEET MEDIA IN DUKUH PAKIS URBAN VILLAGE, SURABAYA CITY: OPTIMALISASI PENCEGAHAN DAN PENANGGULANGAN STUNTING DENGAN MEDIA LEMBAR BALIK DI KELURAHAN DUKUH PAKIS KOTA SURABAYA - Nurvitriana, Nidya Comdeca; Wijayanti , Karunia (Antis-publisher, 2024)
According to the World Health Organization (WHO), in 2017, there were 151 million children, or 22% of children under five years old worldwide who suffered from stunting. Indonesia is classified as a developing country and has more than half of its children experiencing stunting. Based on the results of direct interviews, the facts about the problems in the process of providing education were found to be less effective so that the service providers had a solution to the activity of conducting outreach using flip-sheet media in order to increase effectiveness in providing education. The results obtained from this activity were an increase in knowledge and skills in providing stunting education to the community, facilitated by flip-sheet media.